MEKTEPLERDE ATOM FIZIKASÍ BÓLIMIN OQÍTÍWDÍ JETILISTIRIW JOLLARÍ (Mektep fizika muǵallimlerine metodikalıq járdem) - Jumamuratov, A.J.; Kalilaev, F.K. (SCIENCE and SOCIETY, 2022)
It is analyzed the methods of increasing the effectiveness of teaching in atomic, nuclear and elementary particle physics in schools with the help of innovative technologies.
Keywords: learning technology; planned blocks; Thomson model; Boron postulates; Frank Hertz experiment. Stern-Gerlax experiment; spin